Numerical simulation of liquid nitrogen injection in a container with controlled atmosphere. (November 2019) - Guo, Jiaming; Wei, Xinyu; Du, Xiannan; Ren, Junjie; Lü, Enli
Abstract : The effects of recirculation velocity on the volume fraction of oxygen and the temperature distribution in a container with a controlled atmosphere (CA) by liquid nitrogen injection were investigated. A three-dimensional (3-D) model was developed, and the airflow, heat, and mass transfer in the process of liquid nitrogen injection were simulated. A validation test was conducted to verify the accuracy of the model. The results indicate that improving the recirculation velocity will extend the time of liquid nitrogen injection but will reduce the temperature difference in the container and on the surfaces of fruits and vegetables. Different recirculation velocities have little effect on the distribution uniformity of the oxygen volume fraction. The temperature at the holes on the division plate were all above 0 °C when the recirculation velocity was 8 m/s. The results of this study provide a detailed understanding of air transport in a container, which will be useful for the design and optimisation of transportation containers for fruits and vegetables in a CA.